Molecular progression to cervical precancer, epigenetic switch or sequential model?. Issue 7 (3rd July 2018) - Nedjai, Belinda; Reuter, Caroline; Ahmad, Amar; Banwait, Rawinder; Warman, Rhian; Carton, James; Boer, Sabrina; Cuzick, Jack; Lorincz, Attila T.
Abstract : The evolution of precancerous cervical lesions is poorly understood. A widely held model of cervical intraepithelial neoplasia grade 3 (CIN3) development is sequential progression from normal through CIN1 and CIN2 to CIN3. Another hypothesis, the "molecular switch" model, postulates that CIN3 can evolve directly from human papillomavirus (HPV)‐infected normal epithelium without progressing through CIN1 and CIN2. To shed light on this process, we compared DNA methylation of selected human biomarkers and HPV types in two groups of CIN1: CIN1 that were near or adjacent to CIN3 (adjacent‐CIN1) and CIN1 that were the principal lesions with no CIN3 detected (principal‐CIN1). 354 CIN (CIN1 and CIN3) and normal tissue areas were dissected and typed for HPV from 127 women who underwent loop electrosurgical excision procedures (LEEP). Methylation of genes EPB41L3 and the viral regions of HPV16‐L1/L2, HPV18‐L2, HPV31‐L1, and HPV33‐L2 were determined by a highly accurate quantitative pyrosequencing of bisulfite converted DNA. There was a significant trend of increased methylation with disease grade comparing normal to CIN1 and CIN3 ( p  < 0.0001). Adjacent‐CIN1 predominantly shared the same HPV types as the CIN3, however, methylation differed substantially between adjacent‐CIN1 and CIN3 ( p  = 0.008). In contrast diagnostically principal‐CIN1 had an indistinguishable methylation distribution compared to adjacent‐CIN1 ( EPB41L3: p  = 0.49; HPVme‐All: p  = 0.11). Our results suggest that progression from normal epithelium to CIN1 or CIN3 is usually promoted by the same HPV type but occurs via distinct DNA epigenotypes, thus favoring the "molecular switch" model. Abstract : What's new? Do cervical intraepithelial neoplasias always start at CIN1 and progress to CIN3? Or can CIN3 arise directly from normal epithelium, after HPV infection? The authors investigated by testing DNA methylation in different CINs. They compared CIN1 with CIN3 within the same cervix, and also compared CIN1 adjacent to CIN3 with CIN1 from patients without detectable CIN3. CIN1 and their neighboring CIN3, they found, each had distinct patterns of methylation, despite carrying the same HPV infection. All the CIN1 samples, however, exhibited similar methylation, regardless of the presence of CIN3. This suggests methylation can switch cells directly into a CIN3 state.